Análisis del programa de responsabilidad social: “Belleza por un futuro” de L’oréal Perú según la teoría del valor compartido - Silva Santisteban Maita, María de Fátima (2020)
Since 2016, L’Oréal Peru, in alliance with Pachacutec Foundation, has carried out the ‘Beauty for a better life’ program which is developed through an annual training in five areas of specialization. Providing quality training and offering new perspectives for women in social and economic instability, in the Ventanilla district. By this scenario, the purpose of research was to evaluate the program, based on two aspects: Employment Promotion and the impact within the participants for the 2016 to 2018 program, in terms of loyalty. For that reason, we aimed to analyzed the case study from the perspective of “the Theory of Shared Value” and by the application of surveys to 72 Program’s beneficiaries, in which was found that the levels of employability and loyalty are high; generating by thus a social and business benefit